Real-Time Stability in Power Systems Techniques for Early Detection of the Risk of Blackout - Savulescu, Savu C.; Savulescu, Savu C. (Power Electronics and Power Systems, 2014)
This pioneering volume has been updated and enriched to reflect the state-of-the-art in blackout prediction and prevention. It documents and explains background and algorithmic aspects of the most successful steady-state, transient and voltage stability solutions available today in real-time. It also describes new, cutting-edge stability applications of synchrophasor technology, and captures industry acceptance of metrics and visualization tools that quantify and monitor the distance to instability. Expert contributors review a broad spectrum of additionally available techniques, such as trajectory sensitivities, ensuring this volume remains the definitive resource for industry practitioners and academic researchers in this critical area of power system operations.